How to Make a Constitution? Current Developments and Debates in Turkey - SEN, Ilker GÃ¶khan (Richtmann Publishing, 2012)
It is common wisdom that Turkey, with its divided society, has a long but troubled history with democracy. Especially withrespect to the last three decades, one should remember the making and functioning of the current constitution. Since its adoption in1982, current constitution of Turkey has been a target of condemnations, since it had been a fruit of a military coup dâ€™etat . Falling shortof the current international standards of democracy and rule of law, this Constitution has undergone seventeen amendments. Aconsiderable number of liberalization and democratization packages to the constitution were made during the last eight years of Justiceand Development Party (Adalet ve Kalkô€ƒ•nma Partisi: AKP ) With the electoral victory of the AKP on 12 June 2011, the process of theresolution for Turkeyâ€™s chronic â€œconstitutional problemâ€ took a new pace. As its third term has started, the AKP stated that Turkeyneeded an entirely new constitution and this would be done in a constitution making process, where all segments of the politicalspectrum would be represented. This presentation aims to explore the question of constitution making considering the most recentdevelopments and debates surrounding the present Constitution of Turkey. For this, we will first consider the question of constitutionmaking in terms of constitutional law, as well as political science. Then we will go on to explore the major legal and political problems inthis framework.